Analysis of Factors Causing Material Waste Using the Pareto Method and a Fishbone Diagram in Building Construction Projects - Amelia Ayuni Agustina; Aryati Indah K (Newinera Publisher, 2026)
Material waste is one of the major problems in construction projects that can lead to increased costs, project delays, and reduced project efficiency. This study aims to analyze the factors causing material waste in building construction projects using the Pareto and Fishbone Diagram methods, with a case study of Hotel X Construction Project in West Java. The research employed a quantitative method with a descriptive-analytical approach through field observations, project documentation, interviews, and questionnaires distributed to respondents directly involved in project material management. Pareto analysis was used to identify materials contributing the greatest losses, while the Fishbone Diagram was applied to analyze the root causes of material waste based on factors of man, method, material, machine, and management. The results showed that the total loss caused by material waste reached IDR 32,109,075.00, with D22 reinforcing steel contributing 36,64% and concrete contributing 28,76%, resulting in a cumulative contribution of 65,40%. The main factors causing waste included improper material cutting, weak field supervision, inefficient work methods, material damage during delivery, and suboptimal material management. Based on the findings, waste control recommendations include the implementation of cutting plans, improvement of work supervision, optimization of material storage systems, and enhancement of coordination among project divisions. This research is expected to serve as a reference for improving material use efficiency and minimizing losses in building construction projects.